Hepatic uptake of epirubicin by isolated rat hepatocytes and its biliary excretion after intravenous infusion in rats - Shin, Dae Hwan; Park, Seong Hyeok; Jeong, Sung Woo; Park, Chun-Woong; Han, Kun; Chung, Youn Bok (Archives of pharmacal research, 2014)
Anthracycline anticancer agents are widely used in the cancer chemotherapy for hepatocelluar carcinoma. However, accurate kinetic analyses of the hepatocellular uptake and efflux of the drugs have not been reported. We, therefore, investigated the hepatobiliary transport of epirubicin, an anthracycline derived antibiotic, after intravenous (i.v.) infusion in rats. The hepatic uptake mechanisms of epirubicin were also investigated in isolated rat hepatocytes. To analyze epirubicin levels in the biological samples, we used an HPLC-based method which has been validated for a kinetic study by suitable criteria. The uptake process of epirubicin by the hepatocytes revealed one saturable component, with a K m of 99.1 μg/mL and V max of 3.70 μg/min/10 6 cells. The initial uptake velocity of epirubicin was significantly inhibited in a temperature-dependent manner. The velocity was also reduced in the presence of metabolic inhibitors such as rotenone or carbonylcyanide- p -(trifluoromethoxy)-phenylhydrazone. Substrates for organic anion transporters such as bromosulfophthalein and taurocholate significantly inhibited the initial uptake velocity of epirubicin. We also attempted to determine the hepatobiliary transport of epirubicin after i.v. infusion in vivo. At steady-state after i.v. infusion of epirubicin (10–160 μg/min/kg), the drug was extensively accumulated in the liver, followed by excretion into bile. Furthermore, the CL bile,plasma and CL bile,liver decreased with a corresponding increase in the C ss,plasma and C ss,liver . In conclusion, present studies using isolated rat hepatocytes and in vivo i.v. infusion demonstrate that epirubicin is likely to be taken up into liver cells via organic anion transporting polypeptides, and that its biliary excretion might be mediated via specific transporters.